Late-onset obsessive-compulsive disorder: Risk factors and correlates - Frydman, Ilana; Brasil, Pedro E. do; Torres, Albina Rodrigues [UNESP]; Shavitt, Roseli G.; Ferrao, Ygor A.; Rosario, Maria C.; Miguel, Euripedes C.; Fontenelle, Leonardo F. (Elsevier B.V., 2014)
Background: While a great amount of attention has been paid to early-onset obsessive-compulsive disorder (OCD), there is a dearth of studies on patients showing OCD for the first time at later stages of life. In this study, we aimed at determining possible risk factors/correlates for OCD onset at or after age 40, here termed late-onset OCD.Method: A series of models including several potential variables associated with late onset OCD were tested using a monolayer neural network. To this regard, data from the Brazilian Research Consortium of Obsessive-Compulsive Spectrum Disorders (CTOC) (n = 1001) was employed. For the purposes of this study, we considered a diagnosis of late onset OCD to be present whenever distress and interference associated with OCD symptoms emerged at or after age 40. Different nested models were compared through the Akaike Criteria keeping the variables with p value <= 0.05.Results: Late-onset OCD occurred in 8.6% of the sample. A model including female sex, a history of chronic (>10 years) subclinical obsessive-compulsive symptoms, the co-occurrence of posttraumatic stress disorder (PTSD) after age 40, and a history of recent pregnancy in self or significant others was able to explain a sizeable proportion of late-onset OCD. The general performance of this model, represented by the Maximum Likelihood R2, was 29.4%.Conclusion: Our results suggest that late-onset OCD is more likely to occur in females, in individuals with long periods of subclinical obsessive-compulsive symptoms, and in association with a major traumatic event occurring after age 40 and a history of recent pregnancy in self or in significant others. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Obsessive-compulsive disorder; Clinical course; Onset; Late-onset; Phenotype